Investigation of the thermoelastic phase transformation in a NiAl alloy by molecular dynamics simulation - Ozgen, S; Adiguzel, O (Pergamon-Elsevier Science Ltd, 2004)
The Ni(x)A(1-x) alloys exhibit shape memory effect, for which thermoelastic phase transformations are essential, in the composition range of 60 < x < 65. The analytical studies are very difficult on the thermoelastic phase transformations because these types of transformations exhibit anharmonic behaviour. In order to overcome this difficulty, it is possible to benefit from the molecular dynamics (MD) calculations based on interatomic interaction potentials. In the present study, the interatomic interactions of Ni62.5Al37.5 alloy have been modelled by means of Lennard-Jones potential energy function. A MD cell of 1024 atoms in B2 super lattice has been chosen and the structural changes were investigated on this system with changing temperature. It has been observed that the model alloy exhibits the thermoelastic phase transformation with thermal cycling. A hysteresis has been determined between forward and backward transformation temperatures. The structural analysis is also done before and after the transformation. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: Martensitic-Transformation; Model